Diversity and abundance of termites along altitudinal gradient and slopes in Mount Slamet, Central Java, Indonesia - HERY RATIKNYO; INTAN AHMAD; BAMBANG HERU BUDIYANTO (Biodiversitas Journal of Biological Diversity, 2018)
Pratiknyo H, Ahmad I, Bambang Heru Budianto BH. 2018. Diversity and abundance of termites along altitudinal gradient and slopes in Mount Slamet, Central Java, Indonesia. Biodiversitas 19: 1649-1658. A study on diversity and abundance of termites along an altitudinal gradient and the different slope was done in plantation forest of Mount Slamet. This research aimed to define the species composition along the altitudinal gradient and slope and to define the environmental factors affecting it. The sampling of termites was carried out following standardized belt transects (100 m x 2 m) laid vertically on the altitude of 700 up to 1300 m asl on four slopes. Each 100 m length of the belt transects was divided into 20 sections (5 m x 2 m), and termites were taken in each section from the trees, branches, barks and the ground. Data of termites composition were analyzed for diversity index (Shanon-Wiener, H') and domination index (Simson, D); the correlation among environmental factors with the family were analyzed by multivariate correlation, and then a Canonical Correspondence Analysis (CCA) was used to define the most associated environmental factor to the diversity and abundance of termites. A total of 7349 individuals belonging to 11 species in nine genera, five subfamilies, and two families were recorded. Four wood feeder species were Schedorinotermes javanicus, Macrotermes gilvus, Odontotermes javanicus and Microtermes insperatus, while humus feeder was Capritermes samarangi, Procapritermes stiger, Nasutitermes matangensis, N. matangensiformis, Bulbitermes spp., and the soil feeders were PeriCapritermes javanicus and P. dolichocephalus. Based on the Shanon-Wiener index, the Western Slope was the highest in diversity with five main environmental factors (altitudes, maximal rainfall, N content, manure application and light intensity) the most influencing while the CCA ordination showed that the canopy closure and light intensity were the most associated factor to the diversity and abundance of termites. In conclusion, the slopes caused the species richness differently with the most associated environmental factors was the canopy closure and light intensity.